2021
DOI: 10.1101/2021.07.14.21260510
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of kinetics of immune responses to SARS-CoV-2 proteins in individuals with varying severity of infection and following a single dose of the AZD1222

Abstract: Background: While there have been many studies characterizing the IgG and IgA responses to different SARS-CoV-2 proteins in individuals with natural infection, the induction of IgG and IgA to different viral proteins in vaccinees have not been extensively studied. Therefore, we sought to investigate the antibody responses to SARS-CoV-2 following natural infection and following a single dose of AZD2221, in Sri Lankan individuals. Methods: Using Luminex assays, we characterized the IgG and IgA responses in patie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…For most samples, the scores obtained were one or two units higher when the Wuhan IH4-RBD reagent was used than those with the IH4-RBD-Delta reagent (Figure S3). This is consistent with a previous report that, in vaccinated people, HAT titers obtained with the IH4-RBD-Delta tend to be lower than with the IH4-RBD-Wuhan (Jayathilaka et al, 2021), and with the fact that, at the time of our study, most people in the French population had antibodies due to being vaccinated and not as a consequence of a previous infection by the SARS-CoV2 virus (retrospective analysis of clinical information on our cohort of 60 blood samples revealed that only three samples were from patients who had ever had a positive PCR test for SARS-CoV-2 (see data file and Figure S3).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For most samples, the scores obtained were one or two units higher when the Wuhan IH4-RBD reagent was used than those with the IH4-RBD-Delta reagent (Figure S3). This is consistent with a previous report that, in vaccinated people, HAT titers obtained with the IH4-RBD-Delta tend to be lower than with the IH4-RBD-Wuhan (Jayathilaka et al, 2021), and with the fact that, at the time of our study, most people in the French population had antibodies due to being vaccinated and not as a consequence of a previous infection by the SARS-CoV2 virus (retrospective analysis of clinical information on our cohort of 60 blood samples revealed that only three samples were from patients who had ever had a positive PCR test for SARS-CoV-2 (see data file and Figure S3).…”
Section: Resultssupporting
confidence: 93%
“…HAT-field works with Delta-variant IH4-RBD Our IH4-RBD reagent was designed to present the RBD sequence of the original Wuhan variant (residues 340-538 of the S protein; (Townsend et al, 2021). At the time of our study, however, a large proportion of the SARS-CoV-2 viruses circulating in France belonged to the Delta variant lineage (see epidemiological report here ), which has two mutations in the RBD domain (L452R and T478K in the B.1.617.2 strain) (Ertesvåg et al, 2021;Jayathilaka et al, 2021). We therefore wanted to compare the results obtained with the IH4-RBD-Wuhan reagent (used above) with a reagent that incorporates the two mutations in the Delta variant, IH4-RBD-Delta.…”
Section: Validation Of the Hat-field Protocolmentioning
confidence: 99%
“…For such an individually-based approach, HAT would seem to be a particularly appropriate solution since it is a very simple and cheap test based on the binding of antibodies to the RBD domain (Joly and Maurel Ribes, 2022; Townsend et al, 2021), which are those with neutralizing activity. Furthermore, because the only reagent in HAT simply comprises small amounts of soluble IH4-RBD protein, the hemagglutination test can be very easily adapted to detect antibodies binding to variant forms of the virus (Jayathilaka et al, 2021).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…The HAT (HemAgglutination Test) method is based on a single reagent, IH4-RBD, which binds to human red blood cells (RBC) via the IH4 nanobody specific for human Glycophorin A and coats them with the RBD domain of the SARS-CoV-2 virus (Townsend et al 2021). HAT has a sensitivity of 90% and specificity of 99%, and is now used by several laboratories worldwide for epidemiological and clinical studies (Ertesvåg et al, 2021; Jayathilaka et al, 2021; Jeewandara et al, 2021; Kamaladasa et al, 2021). To be able to perform HAT on whole blood with the sensitivity and simplicity which we set out the reach, and to attempt to make it quantitative, various modifications and improvements had to be tested, and in order to do this, we felt that we needed a simple quantitative test that would allow us to evaluate the amount of antibodies present in the whole-blood samples we were using more simply and cheaply than by using ELISA or CLIA.…”
Section: Introductionmentioning
confidence: 99%